Technological inroads into understanding city children's natural life-worlds. Issue 2 (3rd March 2016) - Freeman, Claire; van Heezik, Yolanda; Stein, Aviva; Hand, Kathryn
Abstract : Maps and mapping are integral elements in the methodological toolbox used by children's geographers studying children's environmental relationships. The advent of new technologies, particularly computer-mapping software, offers immense potential for enhancing understanding and representation of children's everyday spatial relationships. Computerised mapping tools appeal to children and offer new and exciting applications where children can directly demonstrate their ecological knowledge providing evidence that can be used to challenge commonly held notions that city children are disconnected from nature. This paper explores the development of a computer-mapping interface, combining aerial photos and GIS. We argue that the appropriate application of child-oriented methods allows children to demonstrate carefully, meaningfully and effectively their knowledge of nature as it occurs at the micro-scale in their neighbourhoods and in their lives.